Cytokeratin 7 and Cytokeratin 19 Expressions in Oval Cells and Mature Cholangiocytes as Diagnostic and Prognostic Factors of Cholestasis - Dyonesia Ary Harjanti; Ening Krisnuhoni; Santoso Cornain (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: The activity of liver progenitor cells as bipotent liver stem cells, such as the oval cells, has been observed. The presence of oval cells and mature cholangiocytes forming hepatobiliary ductules may be applied to distinguish extrahepatic and intrahepatic cholestasis of the infants. Method: This cross sectional study was performed on 40 paraffin-embedded sections consisting of 2 groups of 20 cases with extrahepatic and intrahepatic cholestasis of the infants from histophatological examination in Cipto Mangunkusumo hospital Jakarta between January 2000 and September 2011. The liver fibrosis grading was reevaluated by hematoxylin and eosin and also trichrome staining. The specimens were tested by immunohistochemical staining for cytokeratin (CK) 7 and CK 19 expressions in oval cells and mature cholangiocytes. The correlation between CK7/CK19 expressions in oval cells and liver fibrosis were analyzed by Spearman’s correlation test. Results: Expressions of CK7 and CK 19 on oval cells and mature cholangiocytes performed in hepatobiliary ductules, were significantly higher in extrahepatic than intrahepatic cholestasis with p 0.05. CK7 and CK19 expressions in oval cells showed strong correlation with the degree of liver fibrosis with r = 0.793; p 0.05 for CK 7 and r = 0.827; p 0.05 for CK 19. Conclusion: Expressions of CK7 and CK19, in oval cells and mature cholangiocytes, were higher at extrahepatic than intrahepatic cholestasis. Expressions of CK7 and CK19 in oval cells were directly proportional to the degree of liver fibrosis in cholestasis of the infants.   Keywords: cholestasis, oval cell, cholangiocytes, fibrosis, CK7, CK19